KEMITRAAN PT EAST WEST SEED INDONESIA DENGAN PETANI DALAM USAHATANI BENIH WALUH DI DESA TEGALREJO KECAMATAN TEGALSARI KABUPATEN BANYUWANGI - Nany Ela Susanti; Rudi Hartadi; Joni Murti Mulyo Aji (University of Jember, 2015)
Pumpkin is a horticulture plant that can be used as economic source of income for the people of Indonesia. Pumpkin is a commodity that has a high economic value since the pulp, leaves and seeds can be used as an economic resource. In some areas pumpkin becomes a main source of income. One of the places that develop pumpkin plant is Tegalrejo Tegalsari Banyuwangi in partnership with PT East West Seed Indonesia to produce seeds of pumpkin which aims to improve their income.The study is conducted in Tegalrejo Tegalsari Banyuwangi intentionally (purposive method). Sampling method is using simple random sampling method (simple random sampling) by respondents 36 people. The data used are primary data and secondary data. Methods of analysis is using descriptive analysis, scoring analysis, revenue analysis and multiple linear regression analysis.The results shows that (1) partnerships pattern undertaken by pumpkin seed farmers with PT East West Seed Indonesia is subcontracting partnership with seeing obedience both sides declared a success or a win-win solution. (2) The level of motivation of type LA003 pumpkin seeds farmers in Tegalrejo Tegalsari Banyuwangi in partnership is hight with a score of motivation (83%). (3) The average income per hectare pumpkin seed farm is Rp 16.665 130,56 and the value indicates an advantage for farmers. (4) factors affecting pumpkin seeds farm income are significant at the level of 95% is the cost of fertilizer, the cost of TK, the amount of production, and that is significant at the level of 90% is the cost of fertilizer, the cost of TK, land area, the amount of production and age of farmers, whereas no significant effect is the cost of drugs, long-standing partner, and the level of motivation. Keyword :partnership, motivation, income, factor income